Dasar-Dasar Teknik Bernyanyi Opera - Theodora Sinaga (Universitas Negeri Medan, 2018)
This study aims to analyze, Technique of Singing in Opera. The purpose of this research is to know Technique of Singing. The theory used is vocal technique, sound processing, sound formation, breathing, frasering, head voice, powering, vibrato, interpretation, singing, opera, aria, The method used in this research is qualitative descriptive method, namely a research method that aims to describe in detail and clearly about a phenomenon that became the focus of research. On the basis of it can be started that the overall appearance of Diana Damrau is interconnected to build on the builder’s point to make the appearance of Diana Damrau towards spectaculer.